Feasibility of implementing collaborative decision skills training among veterans with psychosis: a qualitative study guided by the practical, robust implementation and sustainability model - Emily B. H. Treichler; Jennisa Bangal; Lauren McBride; Elissa Gomez; Sydney Seaton; Joanna Jain; Han Trieu; Eric Granholm; Gregory A. Light; Borsika A. Rabin (Frontiers in Health Services, 2026)
Background Collaborative Decision Skills Training (CDST) is a promising group intervention for adults with serious mental illness (SMI) intended to increase collaborative decision-making (CDM) at the patient-clinician level. CDST previously underwent a systematic, community-engaged mixed methods adaptation to increase fit and feasibility for Veterans with psychosis at VA Psychosocial Rehabilitation and Recovery Centers (PRRCs). This qualitative study applies the Practical, Robust Implementation and Sustainability Model (PRISM) framework to identify the fit and feasibility of the adapted version of CDST within VA PRRCs for Veterans with psychosis. Methods Nine Veterans with psychosis and two clinicians who participated in a CDST pilot trial at a VA PRRC provided feedback about CDST in qualitative interviews. PRISM-mapped guides were used to administer semi-structured interviews and develop qualitative codes. Following the initial coding of interviews, four analysts applied a systematic thematic approach to identify themes within each PRISM domain, inclusive of the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) evaluation framework housed within PRISM. Identified themes were then reviewed by three analysts who reached consensus on the final themes to be presented in this paper. Results Five cross-cutting themes were identified across PRISM domains, capturing CDST's conceptual alignment with PRRCs and the recovery model; variability of Veteran and clinician interest despite fit or effectiveness; the need for structural integration for sustainability; mixed perceptions of CDST's virtual format; and challenges with at-home practice completion. Additional themes were identified under PRISM Intervention Characteristics, Implementation and Sustainability Infrastructure, Recipients, and all RE-AIM outcomes which inform Veterans' and clinicians' implementation viability and sustainability. Conclusions Application of the PRISM framework facilitated identification of multilevel determinants for CDST feasibility. CDST shows promising alignment with the recovery model and the structural approach to care at PRRCs, but delivery mode and auxiliary practice group require adjustment to support CDST's sustainability.